An Islamic Leadership Model Based on Umar Bin Khattab’s Servant Leadership in The Management of Modern Islamic Schools (Madrasahs) - Novita, Rizki; Munir, Hamzatul (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
This study examines and contextualizes the servant leadership model exemplified by Umar ibn al-Khattab and its application in the management of modern Islamic schools (madrasahs). The research aims to identify key leadership values justice, simplicity, participation, accountability, and exemplary behavior and formulate a practical model for their integration into Islamic Education Management (Manajemen Pendidikan Islam/MPI). Using a descriptive qualitative approach grounded in a naturalistic paradigm, the study combines literature review and case studies conducted in two South Sumatran madrasahs to explore how these values manifest in real-world managerial practices. Data were gathered through library research, participant observation, in depth interviews, and document analysis, with thematic coding and triangulation ensuring the validity of findings. The results reveal that Umar’s leadership principles are operationalized in madrasahs through equitable evaluation policies, modest resource allocation, participatory planning, transparent accountability, and moral role modeling by school leaders. These practices enhance institutional integrity, improve governance efficiency, and strengthen moral-spiritual culture within educational environments. The study contributes theoretically by linking classical Islamic leadership philosophy with contemporary managerial frameworks and practically by offering a values-based model applicable to policy development and leadership training. While the limited sample restricts generalizability, this research lays the groundwork for future studies employing mixed or action research to assess the measurable impact of Umar-inspired leadership on institutional performance. Ultimately, the findings affirm that revitalizing Islamic servant leadership offers a strategic pathway toward ethical, participatory, and sustainable educational governance in the era of Education 5.0.